Study of pangenomic variations in the evolution of the sister species Anopheles gambiae and Anopheles coluzzii - (:unkn) unknown (My University, 2023)
The Anopheles gambiae species complex comprises at least nine sibling mosquito species known to include the most significant vectors of human malaria in Africa. Morphologically indistinguishable, these species exhibit incomplete reproductive isolation, and are ecologically highly diversified. The most important vectors, An. gambiae and An. coluzzii, are also the youngest species and demonstrate remarkable ecological flexibility, with extensive and overlapping distributions across various biomes in sub-Saharan Africa. This ecological flexibility is believed to stem from three major genomic properties: (i) these species possess a high number of chromosomal inversions in their genome involved in adaptation, insecticide resistance, and pathogen resistance; (ii) their genomes also harbor a remarkable density of single nucleotide polymorphisms (SNPs); (iii) and these two species, along with the seven other members of the species complex, have shown a strong propensity for hybridization and interspecific gene flow, impacting their genomes and connecting the genetic pools of species on the macroevolutionary scale of the complex.Genomic data generated by the Anopheles gambiae 1000 Genomes Project (Ag1000G) have enabled the study of diversity, local adaptation, and speciation in these species, primarily focusing on the analysis of nuclear genome SNPs. The overall objective of this thesis is to understand the contribution of other sources of genomic variations (mitochondrial and structural), which have been largely underexplored until now.In the first chapter of this thesis, we investigated the factors and processes that have shaped the evolution of the mitochondrial genome in An. gambiae and An. coluzzii. Presumed to be selectively neutral and representative of population and species evolution, we demonstrate that complex evolutionary processes, including natural selection and introgression, have shaped its evolution.Beyond SNPs, the study of chromosomal inversi
Keywords: African Research